Analysis of the Implementation of MSME Regulations in the Digitalization of Palm Sugar Marketing: An Action Research Study Following Community Service in Sikeben Village - Lutfiah Rahmah; Nazmi Lail Rahman Harahap; Dinda Aulia; Azizah Nur Khalisah Daulay; M. Fakhriza (Academic Solution Publisher, 2025)
This study discusses the development of palm sugar MSMEs in Sikeben Village through the use of digital technology. Palm sugar MSMEs play an important role in the local economy, but traditional marketing methods limit their market reach. This study used observation, interviews, and project development methods during the implementation of the 2025 Community Service Program (KKN) by students of the State Islamic University of North Sumatra. The results show that the palm sugar production process is still carried out traditionally, but business actors face obstacles in terms of digital skills and a lack of marketing innovation. As a solution, an integrated sales website with social media was designed to facilitate ordering and expand the market. In conclusion, digital transformation can be an effective strategy to increase the competitiveness of SMEs, but ongoing assistance and training are needed so that this program provides long-term benefits for the village economy..